A randomised study of evaluation of antiulcerogenic activity of quercetin in rats - Shaik, Altaf Hussain; M., Venkata Siva Prasadu (International Journal of Basic & Clinical Pharmacology, 2018)
Background: Peptic ulcer is very common disease. Peptic ulcer results probably due to an imbalance between aggressive factors (acid, pepsin, H. pylori) and defensive factors (gastric mucus, prostaglandins and bicarbonate secretion). Whatever may be the cause of peptic ulcer, it is the gastric acid that prevents ulcer healing and maintain the ulcer. Therefore, most of the drugs available for treatment of peptic ulcer either neutralize the secreted acid or decrease the acid secretion. Methods: The study was conducted on albino rats (Wistar) of 200-250g and maintained under standard conditions (room temperature 24-27oC and humidity 60-65%) with 12h light and dark cycle. The food in the form of dry pellets (Amrut Lab., hyd) and water were available ad libitum. The animal experiments were approved by the ethics committee of the institute. Results: In pyloric ligation model, the rats pre-treated with quercetin showed highly significant protection (p <0.001) when compared to control group and significant protection when compared to ranitidine pre-treated group (p <0.05). In indomethacin model, both quercetin and ranitidine pre-treated groups showed significant protection when compared to control group (p <0.01). Conclusions: In conclusion, it appears that quercetin possess anti-ulcerogenic principles like flavanoids, phenolic compound and caratinoid. These phytoconstituents provides protection against gastric mucosal damage induced by pylorus ligation, aspirin and ethanol, through inhibition of gastric acid, pepsin, histamine and free radical and stimulation of mucus secretion.